Психоанализдегі аутоагрессивті мінез-құлық мәселесі туралы - Sultanov, A. B.; Kazhimova, K. R. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2022)
The article is devoted to a review and discussion of psychoanalytic theories of the formation of autoaggressive and especially suicidal behavior phenomena. Freud’s first observations of self-objectification in melancholic depression were followed by contributions from object relations theorists and self psychology, emphasizing primarily the role of narcissistic rage and ego-vulnerability. In addition to the above theories, the paper also analyzes the views of M. Klein, O. Kernberg, and H. Rosenfeld. The peculiarity of this work is that it covers little-known in Kazakhstani psychology concepts of autoaggressive, namely suicidal behavior formation, such as P. Fonagy’s theory of mentalization, influence of family dynamics, role of shame and self-esteem fluctuations. Particular attention is paid to the consideration of the emergence and development of and, in particular, suicidal tendencies. The distinction between reactive suicide and chronic suicidal preoccupation is highlighted. In the final part of the article, the actual data of empirical testing of some of the concepts described are presented. On the basis of the studied material, the author offers generalized conclusions that will help to better understand and structure the available information on this issue, as well as justify further study of the problem of autoaggressive behavior. Key words: autoaggressive behavior, suicide, psychoanalysis, object relations theory, self psychology